Layanan e-learning Pembelajaran dan Evaluasi Materi Dasar Iqr’a pada Madrasah Ibtidaiyah Swasta Tarbiyah Wewit - Salsa Sukma; Edwin A.U. Malahina; Menhya Snae (Universitas Kristen Immanuel, 2023)
Abstract - The demands in this era of globalization refer more to technological developments for innovation and creativity in the world of education in order to be able to reform education and learning. With these innovations, it can improve the quality of education, especially in the learning process. E-learning is learning using electronic assistance, in addition to using e-learning must also use internet media. E-learning is flexible, students can study anywhere without any time limit. The purpose of this study is to describe the website-based e-learning process in thematic learning at MI Tarbiyah Wewit and describe the positive impact of website-based e-learning in thematic learning at MI Tarbiyah Wewit. The results showed that in the website-based e-learning process in thematic learning the teacher used the website as a medium to deliver material and evaluate lessons to students. In addition, teachers also use the website as a medium to collect student assignments. Website-based e-learning in thematic learning has several positive impacts at Madrasah Ibtidaiyah Tarbiyah Wewit. Some of these impacts are increased student learning outcomes and high enthusiasm of students in participating in learning and training students' social discipline attitudes. Keywords - E-Learning, Madrasah Ibtidaiyah, Website